PENGEMBANGAN BAHAN AJAR TEKS NEGOSIASI DENGAN PENDEKATAN KONTRUKTIVISME BERBASIS KECAKAPAN PERSONAL PADA SISWA - Iib Marzuqi; Laila Tri Lestari; Fransiska Angela Larasati; Nida Yanti (PENTAS : Pendidikan Bahasa dan Sastra Indonesia, 2021)
Based on this background, the objectives of this study are as follows (1) to determine, (2) to determine practicality, and (3) to determine the effectiveness of Negotiation Text teaching materials with a constructivism approach based on personal skills in class X SMA Persatuan Kedungpring Lamongan. Based on the process of developing teaching materials, there are steps (1) designing teaching materials, (2) expert validation, (3) design improvements, and (4) product trials. The researchers used research and development (R&D) methods. The model for developing teaching materials uses the Borg & Gall model which is adapted to the Constructivism approach. The research subjects were selected according to the needs, namely, (1) expert on validity, (2) expert on practitioner, (3) expert on effectiveness. The type of data selected is the result of validity from experts on validity, expert practitioners, and experts on effectiveness with experimental methods.